A network analysis of nomophobia among Chinese adolescents: Differences in gender and developmental stages - Wei Hong; Jiabin Liu; Ru-De Liu; Yi Ding; Xiantong Yang (Computers in Human Behavior Reports, 2025)
Nomophobia (no-mobile-phone phobia) refers to anxiety and discomfort caused by being out of contact with mobile devices or mobile connectivity. Although nomophobia was conceptualized as comprising four dimensions with multiple symptoms, previous research has often treated nomophobia as a unitary construct, overlooking the complex interplay among individual nomophobia symptoms and subgroup-specific patterns. To address this gap, this study aims to employ network analysis and network comparison tests to identify the central symptoms of nomophobia and examine differences in symptom networks across gender and developmental stages. A cross-sectional survey was conducted with 2475 Chinese adolescents, including primary, middle, and high school students. The results identified that the symptoms – “not stay up-to-date”, “others not reach me”, and “keep in touch” exhibited relatively high strength centrality within the overall nomophobia network, indicating that they were more directly and consistently connected with other symptoms. However, symptoms centrality varied across gender and developmental stages: “disconnected from online identity” was especially central among females, and “not look up information” was especially central among primary school students. Network comparison results showed that females exhibited stronger overall symptom connectivity compared to males. These findings advance theoretical understanding of nomophobia as a dynamic network of interrelated symptoms, with certain symptoms as central symptoms, and offer practical implications for designing targeted digital mental health interventions for adolescents.